Readiness Assessment of Artificial Intelligence Driven Tax Administration 3.0 in Nigeria - Akhator, Idaehor Karen; Akadakpo, Adefunke Bukola (NIU Journal of Management Sciences, 2026)
This research paper examines the impact of artificial intelligence (AI) technologies in the form of machine learning, big data analytics, blockchain and robotic process automation on tax administration in Nigeria. Literature have been reviewed from various scholarly journals which exposes that emerging technologies, particularly through AI, enhances tax collection and in essence tax administration processes. Though several studies show a positive relationship, however challenges tend to persist, especially in developing economies in Africa regarding the implementation and integration of these technologies. There is a universal development toward digital tax administration 3.0, highlighting the significance of frameworks that are regulatory especially in Nigeria that is still on 2.0. Research carried out shows that Nigeria is emerging in the use of automation in its tax administration process due to challenges such as lack of significant investment in infrastructure, legal and regulatory frameworks surrounding AI and robotisation, digital illiteracy and resistance to adopting new technologies on the path of the taxpayers and tax practitioners. This research shows that AI can revolutionize tax administration globally by increasing efficiency and accuracy, however addressing the associated risks such as cybersecurity threats, data security, ethical and legal issues and complexity of implementation problem is important especially in a developing country like Nigeria. As tax authorities continue to explore AI's applications, changes and adaptations will be essential in the long run. Keywords: Artificial intelligence, Emerging technologies, tax administration, challenges of AI, practical applications of AI.